The Role of Social Capital in Improving School Quality - Fitriana, Fitriana; Khairani, Cut; Fitrah, Hariki (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
This research aims to explore the role of social capital in improving school quality at Pegasing 10 Public Elementary School, Central Aceh Regency. This type of research is qualitative research with a descriptive approach. The informants in this research consisted of school principals, teachers and students. Data collection techniques through observation, interviews and documentation. Research data was analyzed through data reduction, data display and drawing conclusions. To ensure the validity of the data, data triangulation is carried out. The results of the research are social capital regarding cooperation carried out at Pegasing 10 Public Elementary School, namely by collaborating with various agencies, namely (1) education services such as distribution of boss funds, teacher promotions, school infrastructure, increasing teacher competency, (2) health services/ health centers such as socializing healthy lifestyles, immunizations (3) police such as socializing drug education. (4) mobile libraries such as book grants (5) school committees such as supporting school programs, supervising school activities, (6) community: participation in social activities (7) parents through the development of student learning outcomes and disbursement of scholarships.